PENGARUH VARIASI STATOR TURBO BLADE TERHADAP KEKUATAN DORONG TURBOJET DRIVE PRODUK 3D PRINTING MATERIAL ST-PLA - Nori Farandi Nori; Dedy Ramdhani Harahap; Hasdiansah Hasdiansah (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Turbojet drive or water jet as we know today that turbojet drive technology is a marine system that produces water jets for propulsion. However, the thing that must be considered is the thrust generated by the propeller because of a problem that is often discussed. The purpose of this study was to determinet the effect of variations of the turbo stator on the trust of the tubojet drive using the ST-PLA 3D printing material.in this study, the turbojet drive design method uses the concept of an outboard engine with the help of tools and hanging scales to get the value of the thrust so that it can be analyzed later. This study compares 3 forms of turbo stator, namely 4 Blade, 6 Blade and 8 Blade, based on the results of this study it was found that the variation of the turbo stator has a major influence on the thrust of the turbojet drive with 3D printing product ST-PLA material. The test results show that the 8-blade turbo stator has the highest thrust with an average value of 44.145 N and the 4-blade turbo stator has the lowest thurst with an average value of 24.525 N. Besides, this data can also be used as a reference for development of a turbojet drive according to the desired speed with the selection of a turbo stator variation that has been tested.